Parental Rights for Lesbian, Gay, Bisexual and Transsexual Persons: A Comparison Between the European and Inter-American Systems of Human Rights - Lauzon, Jolane (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2019)
This article addresses the question of parental rights for lesbian, gay, bisexual and transsexual persons (LGBT). Through an analysis of the relevant jurisprudence of the Inter-American Court of Human Rights and the European Court of Human Rights, it will look at the right to a family, the right to privacy and the right to non-discrimination, since these rights are the ones that are always invoked by the petitioners. More precisely, this article will look at the question of adoption for homosexual individuals and same-sex couples, as well as the issue of children custody rights.